COVID-19-Related Stressors and Mental Health Among Chinese College Students: A Moderated Mediation Model - Han, Zaichao; Tang, Xiujuan; Li, Xiaoshan; Shen, Youtian; Li, Li; Wang, Jingjing; Chen, Xiaowei; Hu, Zhijun (Frontiers in Public Health, 2021)
This study aims to examine the relation between COVID-19-related stressors and mental health among Chinese college students during the pandemic outbreaks, and the possible mediator or moderator between them. Five hundred and fifty Chinese college students were invited to complete an anonymous survey, and the data were analyzed with SPSS 16.0 software. The results shows that the number of stressors has a negative direct and indirect (through risk perception of being infected with COVID-19 disease) impacts on college students' mental health. Adaptive coping is a protective factor of students' mental health, and could be regarded as a buffer that attenuates the negative effect of the COVID-19-related stressors on risk perception of being infected with COVID-19 disease (or mental health). With regard to demographic variables, females, junior and senior students, or students whose family residence was worst hit by the pandemic tend to report poorer mental health during the pandemic outbreak. These findings enrich our understanding about the impact of the COVID-19 pandemic on college population and have implications for university counseling services during times of acute, large-scale infective disease outbreaks.